The integration of sustainability in municipalities in South Africa: an evaluation of an Eastern Cape district municipality's water supply distribution systems - Maxwele, Zukani (Rhodes University, Faculty of Commerce, Rhodes Business School)
The Constitution of the Republic of South Africa mandates municipalities to provide sustainable services to communities, particularly those responsible for water and sanitation. Despite this obligation, many communities in the Oliver Reginald Tambo District Municipality (ORTDM) face prolonged water interruptions due to challenges with infrastructure. This study has assessed the ORTDM's efforts to integrate sustainability principles into its water supply distribution systems development programmes. Essentially, it aimed to evaluate whether and how ORTDM integrates social, environmental, economic, engineering, and project management sustainability principles into its developmental initiatives. Grounded in the backdrop of global sustainable development imperatives, particularly the Triple Bottom Line (TBL) concept, the research explored challenges and considerations within local government in pursuit of sustainability in water infrastructure development. Utilising a qualitative research approach within a post-positivism paradigm, the study employed semi-structured interviews and document analysis as primary data collection methods, emphasising triangulation for research validity and ethical considerations throughout the study. Although the initially planned sample size was 12 participants, the study successfully interviewed seven municipal officials from ORTDM's water and sanitation services delivery department, achieving a participation rate of 58%, which aligns with qualitative research standards. Findings from document analysis and interviews were categorised based on identified sustainability principles, highlighting strategies adopted and challenges encountered by ORTDM, including opportunities available for ORTDM. The study reveals that while ORTDM has made efforts to integrate sustainability principles, numerous challenges, including financial and natural resource constraints, organisational capacity limitations, inadequate infrastructure planning and maintenance, and socio-economic challenges, have hindered desired outcomes. Additionally, issues like vandalism, theft, biodiversity loss, and fragmented water conservation strategies exacerbate sustainability integration challenges. To address these barriers, the study recommends prioritising management approaches to enhance sustainability integration in ORTDM's water services. Drawing on resilience theory, the study further proposes integrating resilience principles into planning, design, and management processes to improve organisational and system resilience, thus ensuring reliable and sustainable water services. The study emphasises the importance of interdisciplinary collaboration and innovative solutions in achieving resilient, equitable, economical, and environmentally responsible water supply distribution systems.
Keywords: Sustainable development -- South Africa -- Eastern Cape; Municipal services -- South Africa -- Eastern Cape; Water resources development -- South Africa -- Eastern Cape; Sustainability